Mit veränderten Reprisen: The Practice of Varying Repeats - Beghin, Tom; Orpheus Historical Piano Summer Academy 2023 Orpheus Instituut, Ghent, Belgium (Orpheus Instituut, Ghent, Belgium Tom Beghin, 2023)
Film documentary, 43 minutes, in English, German, and French, with English subtitles. Featuring Tom Beghin, Juliane Brandes, Benjamin Steens, Christophe Alvarez, Olha Dotsenko, Andrei Hadap, Wei Lee, Otto Popescu, and Tomasz Ritter. In the summer of 2023, a workshop was held at the Orpheus Institute, Ghent, Belgium, around the practice of varying repeats. Six young keyboardists from around the world gathered around the clavichord and fortepiano to familiarize themselves with CPE Bach’s unique opus of “Sonatas with Varied Reprises” (1760) as well as Mozart’s six early keyboard sonatas, K. 279–284 (1774–75). As today’s performers of classical keyboard sonatas, what happens when we submit ourselves to a once lively expectation of continuous variation? How do we navigate the materiality of a printed score? What are the limits of “writing in” our variants and at what point do we feel like starting over—indeed, creating a new edition altogether? The film follows participants and coaches as they look for answers to these questions, reflecting on their experience during a ten-day experiment of embellishment, variation, and “improvisation.”
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850